A Proposed Conceptual Framework to Understand the Adjustment Processes of People Affected by Dementia in Vietnam and Their Associated Personal and Structural Factors - Nguyen Thu Trang, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Vietnam is among the fastest-aging countries in the world, and dementia has emerged as a significant threat to the well-being of older adults. This paper aims to develop a conceptual framework to understand the adjustment process of individuals affected by dementia in urban areas of Vietnam. Drawing on existing theories and empirical evidence, the proposed framework seeks to explain how family caregivers adjust caring for older adults with dementia in the specific cultural and social context of Vietnam, and what factors influence this adjustment. The framework consists of three key components: (1) the core adjustment process of family caregivers, (2) influential factors at the personal level, and (3) influential factors at the structural level. These components interact as part of a comprehensive system. Importantly, this conceptual framework contributes to the theoretical foundation for future studies and may be applicable to research on the adjustment processes of family caregivers dealing with illness situations—particularly neurological disorders like dementia—in Vietnam and other contexts with similar cultural values.Received 30th October 2024; Revised 5th February 2025; Accepted 7th April 2025